School nurses’ perspectives on key features of a mobile app to support early identification of adolescent mental health problems: a qualitative study - E. Holmgren Celander; N. Gårevik; Zarina Nahar Kabir; Lisa Ring; Lise-Lott Rydström (BMC Nursing, 2026)
Abstract Background Adolescent mental ill health is increasing globally and in Sweden, with rising levels of stress, anxiety, depression, and sleep problems. Many adolescents do not seek help due to stigma, fear of judgement, and limited mental health literacy. School nurses play a key role in early identification and preventive support. Digital tools may complement relational nursing practices and lower thresholds for help-seeking, but little is known about what features school nurses consider feasible and useful in their daily practice. Objective To explore school nurses’ perspectives on key features and content of a mobile app intended to support early identification and management of mental health problems among high school students. Methods An exploratory qualitative study was conducted using semi-structured interviews with ten school nurses working in upper secondary schools. Interviews were held via Zoom, transcribed verbatim, and analysed using reflexive thematic analysis (RTA). COREQ guidelines informed the study’s design and reporting. Results Two overarching themes emerged. First, Fostering mental wellbeing: the school nurse as a trusted ally in a complex world highlighted how early identification often relies on relational continuity, trust, and interpretation of indirect indicators such as somatic complaints or behavioural changes. Second, Nurturing minds: the digital dance of support and solitude reflected nurses’ belief that a mobile app could support time management, self-regulation, psychoeducation, and accessible communication. Feasibility, however, depended on safeguarding confidentiality, maintaining professional boundaries, preventing workload escalation, and managing the “anonymity paradox,” in which anonymity can both facilitate disclosure and hinder safe escalation. Conclusions School nurses perceive that a mobile app could complement face-to-face care by supporting early identification and self-management among adolescents. Successful implementation requires aligning digital features with relational nursing practice, ensuring ethical governance, and integrating clear escalation pathways. Thoughtfully designed mHealth solutions have potential to strengthen preventive mental health support within school health services. Clinical trial number Not applicable.